Empowering Women through Mosque-Based Gender Education: A Study of Women Ulama Cadre Education Program of Istiqlal Mosque - Tandos, Rosita; Kuba, Amiruddin (El-Usrah: Jurnal Hukum Keluarga, 2026)
Gender equality and justice are critical areas of inquiry, not only within academic discourse but also in shaping practical responses to contemporary issues affecting women. To effectively address these challenges, this study essentially adopt an integrated perspective that draws from Islamic teachings, gender theories, and women's studies. It employed a qualitative methodology using a grounded theory approach to examine an initiative of Women Education Program conducted by Great Mosque of Istiqlal in Jakarta, Indonesia, including gender curriculum, method and collaboration. The program reflects a global outlook and is supported by multi-stakeholder partnerships involving ministries, universities, and organizations at local, national, and international levels. Participants in the study responded to a combination of close and open-ended questions designed to explore their knowledge, perceptions, and experiences with the program. The study aimed to explore the contributions of Mosque–based Women Ulama Education Cadre Program conducted by Grand Mosque of Istiqlal in improving gender-responsive curricula and teaching methodologies, particularly in enhancing women's knowledge, skills, and active participation in social transformation. The analysis was guided by three interconnected theoretical frameworks: Islamic perspective, gender and social welfare theories. It applied an approach of gender education in alignment with the Tri Dharma of Islamic Higher Education under the auspices of the Ministry of Religious Affairs of the Republic of Indonesia.